Spontaneous coronary artery dissection in young female acute coronary syndrome patients: a single-centre retrospective cohort study. Issue 7 (2nd November 2021) - De Roeck, Frederic; Scott, Benjamin; Convens, Carl; Vermeersch, Paul
Abstract: Background: Spontaneous coronary artery dissection (SCAD) is an unusual cause of acute coronary syndrome (ACS), rapidly gaining recognition over the last decade. SCAD occurs predominantly in young, otherwise healthy women and coronary angiogram often lacks typical (atherosclerotic) features. Therefore, SCAD remains notably underdiagnosed. As optimal treatment strategy differs greatly from atherosclerotic ACS, early (differential) diagnosis is crucial. Purpose/Methods: In this paper, all coronary angiograms performed for ACS in women up to 50 years of age were retrospectively reviewed by three independent interventional cardiologists. Results: The obtained insights are comparable to recent literature. SCAD incidence was 26% in this cohort. Left anterior descending coronary artery was the main affected vessel with SCAD subtype 2B as predominant angiographic presentation. Correct diagnosis during index procedure was poor with only 33% accuracy. Nevertheless, a favourable trend over time was noted. Percutaneous coronary intervention success was 56%, as in 44% of patients initial stenting was complicated by progressive dissection. Overall, outcome was excellent with no reported fatalities. Conclusion: SCAD remains an underdiagnosed subtype of ACS and the importance of increasing awareness amongst (interventional) cardiologists needs to be emphasised.